Incidence of Intrahepatic Cholestasis of Pregnancy and Its Impact on Maternal and Neonatal Outcomes: A Systematic Review and Meta-Analysis - Ping Yu; Mei Zhang; Chengen He (Clinical and Experimental Obstetrics & Gynecology, 2025)
Background: This study employed a meta-analysis approach to investigate the incidence of intrahepatic cholestasis of pregnancy (ICP) and its impact on adverse outcomes in both pregnant and postpartum women, as well as neonates. Methods: We obtained studies published from the inception of the PubMed, Cochrane Library, and Web of Science databases through January 2024. A total of 21 original articles were included, reporting on ICP and its associated adverse outcomes in maternal and neonatal populations. The included studies involved 1,497,951 controls non-intrahepatic cholestasis of pregnancy (non-ICP) and 12,262 ICP patients. Sensitivity analyses and evaluations for publication bias were also conducted. Results: The pooled analysis estimated an ICP incidence of 3% (95% confidence interval [CI], 1%–7%), while the meta-analysis demonstrated the following risk ratios: postpartum hemorrhage showed a relative risk (RR, 0.82; 95% CI, 0.69–0.99), whereas significant increases were observed for preeclampsia (RR, 2.39; 95% CI, 2.21–2.59), Cesarean section (RR, 1.28; 95% CI, 1.15–1.42), preterm birth (RR, 2.71; 95% CI, 1.77–4.15), and maternal infection (RR, 3.22; 95% CI, 2.48–4.19). Other outcomes included labor induction (RR, 1.60; 95% CI, 0.51–4.99), gestational diabetes mellitus (GDM; RR, 1.29; 95% CI, 0.83–2.01), stillbirth (RR, 1.25; 95% CI, 0.64–2.42), and small for gestational age (SGA; RR, 1.06; 95% CI, 0.71–1.57), which were not statistically significant. Neonatal intensive care unit (NICU) admission (RR, 1.79; 95% CI, 1.35–2.37), with a significant increase in risk. Conclusions: This meta-analysis demonstrates a global incidence of ICP at 3% and identifies significant associations with adverse maternal and neonatal outcomes. ICP is associated with increased risks of preeclampsia, Cesarean section, preterm birth, maternal infection, and neonatal intensive care needs. Interestingly, a relative risk of postpartum hemorrhage was observed, suggesting the need for further investigation into the underlying mechanisms. Although labor induction, GDM, and stillbirth showed non-significant trends toward increased risk, their clinical relevance persists. These findings underscore the necessity for risk-stratified surveillance in ICP management, emphasizing infection control and preterm prevention, alongside regionally tailored clinical protocols. Registration: The study has been registered on https://inplasy.com/inplasy-2025-3-0132/ (registration number: INPLASY202530132).